A light-converting carrier film for 0BB photovoltaic encapsulation and its preparation method and application
By using a multi-layer coextrusion-formed ultraviolet light bearing film with a converting layer and an adhesive layer formed by multi-layer coextrusion, the problems of poor durability and low efficiency increase rate of the prior art transshipment light bearing film are solved, and the problem of poor durability and low efficiency increase rate of the transfer light bearing film is realized. Higher photoelectric conversion efficiency and durability.
Patent Information
- Application Number
- CN202410105752.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-25
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-01-25
AI Technical Summary
The existing light-to-light bearing film has poor durability, and the efficiency increase rate of battery modules also needs to be improved.
The structure of the ultraviolet absorbing layer, ultraviolet conversion layer and adhesive layer formed by multi-layer coextrusion is used to convert ultraviolet light into red and blue light through the ultraviolet light conversion layer to increase the power generation, and the bonding is enhanced through the adhesive layer. Performance and block water vapor, extending the durability of UV light converter.
The photoelectric conversion efficiency is improved, the durability of the ultraviolet conversion layer is extended, and the peeling force and component efficiency increase rate are improved.
Smart Images

Figure CN117936609B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photovoltaic technology, and in particular to a light-converting bearing film for 0BB photovoltaic packaging, and a preparation method and application thereof. Background Art
[0002] The trend of photovoltaic development has always been high efficiency and low cost, and heterojunction cells have the characteristics of high light conversion efficiency, low temperature coefficient, excellent double-sided power generation rate, etc., and are considered to be the next generation of ultra-high efficiency cell technology with the greatest industrialization potential. The increase in the number of main grids in the cell has increased the shading rate of the cell to a certain extent, reducing the power generation efficiency of the photovoltaic module; and the large amount of silver used in the main grid also increases the cost of the photovoltaic module, so the busbar-free cell interconnection technology has gradually emerged.
[0003] The busbar-free technology refers to setting only the secondary grid lines on the cell, using metal wires as the busbar lines to embed into the carrier film, and then covering the carrier film on the thin grid lines of the cell. During the lamination process, the low-melting-point metal on the surface of the conductor solidifies with the thin grid lines to form an ohmic contact. The busbar-free solar cell module thus obtained has a small conductor diameter, a small shading area, and a small possibility of cold solder joints and leaky solder joints. At the same time, it can reduce the amount of silver paste used, which is beneficial to cost control. The light-converting carrier film is to add a light conversion agent or a light conversion layer to the traditional carrier film, so that the band of the incident light with poor solar cell response (low quantum efficiency) is converted into a band with better response (high quantum efficiency), thereby realizing the maximum utilization of sunlight without changing the structure of the solar cell itself, mainly changing the ultraviolet light in the sunlight into usable red and blue light, thereby increasing the unit power generation. The role of the light-converting carrier film is to give the packaging material the ability to convert light while satisfying the role of the carrier film, so as to improve the photoelectric conversion efficiency of the photovoltaic module.
[0004] However, the durability of existing light-converting carrier films is relatively poor, and the efficiency increase rate of battery modules needs to be improved.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a light-converting bearing film for 0BB photovoltaic encapsulation and a preparation method and application thereof, so as to improve the above-mentioned technical problems.
[0007] The present invention is achieved in that:
[0008] In the first aspect, the present invention provides a light-converting carrier film for 0BB photovoltaic encapsulation, which comprises, in sequence, a UV light absorption layer, a UV light conversion layer and an adhesive layer formed by multi-layer co-extrusion; the thickness ratio of the UV light absorption layer, the UV light conversion layer and the adhesive layer is 1: (1-2): (0.5-3).
[0009] In a second aspect, the present invention also provides a method for preparing the above-mentioned light-converting bearing film for 0BB photovoltaic encapsulation, which comprises: respectively extruding the formula materials of the corresponding layers by multiple extruders, and casting them into films in a multi-layer structure through a dispenser.
[0010] In a third aspect, the present invention further provides a busbar-free solar cell assembly, which includes the above-mentioned light-converting carrier film for 0BB photovoltaic encapsulation.
[0011] In a fourth aspect, the present invention also provides an application of the above-mentioned light-converting carrier film for 0BB photovoltaic encapsulation in the preparation of a busbar-free solar cell module.
[0012] The present invention has the following beneficial effects: a multi-layer structure of an ultraviolet light absorbing layer, an ultraviolet light conversion layer and an adhesive layer formed by multi-layer co-extrusion realizes a multifunctional combination; the ultraviolet light conversion layer gives the carrier film light conversion ability, thereby improving the photoelectric conversion efficiency of the component; the ultraviolet light absorbing layer increases the absorption of ultraviolet light; the adhesive layer improves the bonding performance of the carrier film; at the same time, the arrangement of the ultraviolet light absorbing layer and the adhesive layer sandwiching the ultraviolet light conversion layer blocks water vapor from penetrating into the ultraviolet light conversion layer to a certain extent, thereby extending the long-term durability of the ultraviolet light converter of the ultraviolet light conversion layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0014] Figure 1 A schematic diagram of the structure of a light-converting carrier film for 0BB photovoltaic encapsulation provided by an embodiment of the present invention;
[0015] Figure 2 A schematic diagram of the structure of a busbar-free solar cell assembly provided by an embodiment of the present invention;
[0016] Figure 3 Schematic diagram of the laminated appearance of an embodiment of the present invention.
[0017] Icon: 100-ultraviolet light absorption layer; 200-ultraviolet light conversion layer; 300-adhesive layer; 1-glass; 2-encapsulation film; 3-cell; 4-metal wire; 5-0BB light conversion carrier film for photovoltaic encapsulation. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0019] The following is a detailed description of a light-converting bearing film for 0BB photovoltaic encapsulation provided by the present invention, as well as its preparation method and application.
[0020] The inventors found that the poor durability of the existing light-converting carrier film is due to the fact that the ultraviolet light converter is prone to react under hot and humid conditions, which in turn causes its function to fail or decline. Furthermore, the main reason for its poor durability is that water vapor and oxygen easily penetrate into the light-converting carrier film and come into contact with the ultraviolet tube converter. In view of this, the inventors proposed the following technical solution after research and practice.
[0021] In some embodiments of the present invention, a light-converting carrier film for 0BB photovoltaic encapsulation is provided, see Figure 1 , which sequentially includes a UV light absorbing layer 100, a UV light conversion layer 200 and a bonding layer 300 formed by multi-layer co-extrusion; the thickness ratio of the UV light absorbing layer 100, the UV light conversion layer 200 and the bonding layer 300 is 1:(1-2):(0.5-3), for example, the thickness ratio of the UV light absorbing layer 100, the UV light conversion layer 200 and the bonding layer 300 is 1:1:2, 1:1:0.5, 1:1:3, 1:2:2 or 1:1.5:2, etc.
[0022] The three-layer structure consisting of the ultraviolet light absorbing layer 100, the ultraviolet light conversion layer 200 and the adhesive layer 300 has different functions. The ultraviolet light absorbing layer 100 is conducive to the absorption of ultraviolet light, while the ultraviolet light conversion layer 200 is used to convert the ultraviolet light absorbed by the ultraviolet light absorbing layer 100 and the ultraviolet light directly entering the ultraviolet light conversion layer 200 into red light and blue light to increase the power generation, and the adhesive layer 300 plays a role in giving the carrier film good bonding properties. At the same time, the multi-layer co-extruded three-layer structure can make the layers be well combined together, and the morphological properties of the film are better. The ultraviolet light absorbing layer 100 and the adhesive layer 300 sandwich the ultraviolet light conversion layer 200 in the middle, which to a certain extent blocks the water vapor from penetrating into the ultraviolet light conversion layer 200, thereby extending the long-term durability of the ultraviolet light conversion agent of the ultraviolet light conversion layer 200. In addition, the design of the thickness ratio of the three layer structures also enables the light conversion carrier film to have better module efficiency and cell peeling force.
[0023] Specifically, in order to meet the basic conditions of multi-layer co-extrusion and the functions of the matrix of each layer of the carrier film, in some embodiments, by weight, the ultraviolet light absorbing layer 100 includes 60-90 parts of matrix resin A, 10-30 parts of adhesive resin, 1-5 parts of mixing aids and 0.01-2 parts of ultraviolet light absorber. The ultraviolet light conversion layer 200 includes 60-90 parts of matrix resin B, 10-40 parts of adhesive resin, 1-5 parts of mixing aids, and 0.01-2 parts of ultraviolet light conversion agent. The adhesive layer 300 includes 50-90 parts of matrix resin A, 10-40 parts of adhesive resin, 1-5 parts of mixing aids, and 0.01-2 parts of ultraviolet light absorber.
[0024] Further, in some embodiments, the matrix resin A and the matrix resin B are independently selected from at least one of polyethylene, polyvinyl chloride, polystyrene, polypropylene, ethylene-vinyl acetate copolymer, ethylene-α-olefin copolymer, ethylene-methyl methacrylate copolymer or ethylene-methacrylic acid ionomer. That is, the matrix resin A can be selected from any one of polyethylene, polyvinyl chloride, polystyrene, polypropylene, ethylene-vinyl acetate copolymer, ethylene-α-olefin copolymer, ethylene-methyl methacrylate copolymer or ethylene-methacrylic acid ionomer, or a combination of two or more of these substances can be selected, and the ratio of the combination is not limited.
[0025] The content of vinyl acetate in the ethylene-vinyl acetate copolymer is 10wt% to 33wt%; the olefin in the ethylene-olefin copolymer is selected from one or a combination of two or more of 1-pentene, 1-hexene, 4-methyl-1-hexene, 4-ethyl-1-hexene, 1-octene, 1-decene or 1-dodecene.
[0026] At present, conventional photovoltaic encapsulation films are not suitable for main-grid-free HJT battery modules, and are prone to displacement of the welding strip during the lamination process, and the welding strip and the battery cell are prone to virtual connection. Based on this, in order to solve this problem, in some embodiments of the present invention, the adhesive layer 300 is a pre-crosslinked surface, that is, before covering the photovoltaic module, the adhesive layer 300 is pre-crosslinked by ultraviolet light irradiation, so that the welding strip will not be displaced during covering, and the welding strip and the battery cell are not prone to virtual connection. However, if the conventional carrier film is pre-crosslinked in advance, the adhesive layer 300 is prone to blistering and affecting the performance of the carrier film. Therefore, in response to this problem, the inventor further improved the composition design of the adhesive layer 300, that is, the base resin A in the adhesive layer 300 is selected from polyethylene.
[0027] Furthermore, in order to further improve the durability of the light conversion carrier film, the ultraviolet absorption layer and the adhesive layer 300 need a lower water vapor permeability. Therefore, the matrix resin A in the ultraviolet absorption layer and the adhesive layer 300 is selected from polyethylene; at the same time, the ultraviolet light conversion layer 200 itself also needs to have a lower water vapor permeability, that is, the content of polyethylene in the matrix resin B is at least 70%.
[0028] In some embodiments, both the matrix resin A and the matrix resin B are polyethylene with a melt index of 1 to 6 g / 10 min at 190°C / 2.16 kg. The polyethylene is a linear low-density polyethylene, and the molecular weight of the polyethylene is 1000 to 4000. Compared with ethylene-vinyl acetate copolymer and polyolefin elastomer, polyethylene has a lower water vapor permeability. By using polyethylene particles as the inner and outer layers, it can effectively isolate the intrusion of water vapor and oxygen content, thereby improving the long-term durability of the light conversion agent. The film made of traditional polyethylene material has a low peeling force with the battery cell. Therefore, in some embodiments of the present invention, the light conversion carrier film uses polyethylene with a higher melt index and is blended with an adhesive resin to improve the peeling force.
[0029] Specifically, in some embodiments, the ultraviolet light conversion agent includes a light conversion agent of Eu 3+ Doped rare earth oxides, Pr 3+ Doped rare earth oxides, Nd 3+ Doped rare earth oxides, Sm 3+ Doped rare earth oxides, Gd 3+ Doped rare earth oxides, Tb 3+ Doped rare earth oxides, Dy 3+ Doped rare earth oxides, Ho 3+ Doped rare earth oxides, Er 3+ Doped rare earth oxides, Tm 3+ Doped with rare earth oxide or Yb 3+ At least one of the rare earth oxides is doped. That is, the ultraviolet light conversion agent can be any one of the above substances, or a combination of two or more of the above substances. If a combination of two or more substances is selected, the combination ratio of the multiple substances is not limited.
[0030] In some implementations, in order to make the ultraviolet light conversion agent evenly distributed in the ultraviolet light conversion layer 200 and have better conversion performance, the particle size of the ultraviolet light conversion agent is less than or equal to 2 μm.
[0031] In some embodiments, the adhesive resin includes at least one of a terpene resin or a grafted modified resin, that is, the adhesive resin is a terpene resin or a grafted modified resin, or a combination of the two; the grafted modified resin is obtained by grafting and modifying a base resin and a grafted monomer through a melt reaction of free radical grafting, wherein the base resin is selected from the above-mentioned base resin A or base resin B, and the grafted monomer is selected from one or more of vinyl siloxane, unsaturated monobasic acid, unsaturated dibasic acid or α, β unsaturated carbonyl compound, and the α, β unsaturated carbonyl compound is selected from maleic acid, fumaric acid, acrylic acid, methacrylic acid, α-methyl crotonic acid, cinnamic acid and anhydride, ester or salt derivatives of the above acids or a combination of two or more thereof. The melt index of the adhesive resin at 190°C / 2.16kg is greater than 15g / 10min.
[0032] In some embodiments, the mixed auxiliary agent includes a first auxiliary agent and a second auxiliary agent. The first auxiliary agent includes at least one of phenols or amines, for example, the first auxiliary agent is phenols or amines or a combination of the two; the second auxiliary agent includes one or a combination of two or more of tripropylene trimerisocyanate, trimethylolpropane triacrylate, pentaerythritol tetraacrylate, trimethylolpropane trimethacrylate, triallyl cyanurate or di-trimethylolpropane tetraacrylate.
[0033] In some embodiments, the ultraviolet light absorber includes one or a combination of two or more of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, 2-(2-hydroxy-5-methylphenyl)-benzotriazole, a polymer of succinic acid and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol, or 1-(methyl)-8-(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate.
[0034] As mentioned above, in order to make the light-converting carrier film have certain physical properties and better light conversion performance, in some embodiments, the thickness of the light-converting carrier film for 0BB photovoltaic encapsulation is 20 μm to 400 μm, preferably 50 μm to 100 μm.
[0035] Furthermore, some embodiments of the present invention also provide a method for preparing the above-mentioned light-converting bearing film for 0BB photovoltaic encapsulation, which comprises: using multiple extruders to extrude the formula materials of the corresponding layers respectively, and casting them into films in a multi-layer structure through a distributor. That is, the materials required for each layer are mixed evenly, extruded by multi-layer co-extrusion, cast into films, and then cooled.
[0036] Specifically, in some embodiments, in order to further improve the long-term durability of the carrier film, when extruding the ultraviolet light conversion layer 200, the ultraviolet light conversion agent is first coated with a layer of matrix resin to prepare a master batch, and then mixed with other ingredients before extrusion. Among them, the matrix resin is selected to be coated with a resin material with a low water vapor permeability such as polyethylene, so that even if water vapor, oxygen, etc. enter the ultraviolet light conversion layer 200, it is not easy to contact and react with the ultraviolet light conversion agent, thereby improving the long-term durability of the ultraviolet light conversion agent.
[0037] It should be noted that the raw material ratio of each layer refers to the description of the aforementioned embodiment, which will not be repeated here.
[0038] Based on the raw material ratio of each layer, in some embodiments, in the three-layer co-extrusion operation, the screw temperature corresponding to the extrusion operation of the ultraviolet light absorbing layer 100 is 90°C to 200°C; the screw temperature corresponding to the extrusion operation of the ultraviolet light conversion layer 200 is 100°C to 220°C; the screw temperature corresponding to the extrusion operation of the bonding layer 300 is 90°C to 200°C. During the film casting, the screw temperature of the casting machine is 80°C to 250°C.
[0039] In some embodiments, after the film is cast, embossing, pre-crosslinking and slitting are also performed. For example, the casting and embossing are conventional steel rod embossing processes, the purpose of which is to produce concave and convex points on the contact surface of the film. On the one hand, the embossing operation provides an embedding space for the embedding of the metal wire, and on the other hand, the point contact will prevent the film from shifting with the battery cell during the whole laying.
[0040] In some embodiments, the main operation of pre-crosslinking is to irradiate the adhesive layer 300 with a short-wave ultraviolet lamp in the wavelength range of 200nm to 280nm, with an irradiation energy of 500 to 5000mJ / cm 2 , a grid membrane with a pre-crosslinking degree of 20-50% is obtained.
[0041] Furthermore, some embodiments of the present invention also provide a busbar-free solar cell assembly, see Figure 2 , which includes the above-mentioned 0BB photovoltaic encapsulation light-converting carrier film 5, which, when used with the grid line, has the following matching mode with the battery assembly structure: the 0BB photovoltaic encapsulation light-converting carrier film 5 is arranged on both sides of the battery cell 3, the metal wire 4 embedded in the adhesive layer 300 and the fine grid line of the battery cell 3 are solidified together to form an ohmic contact, and then the 0BB photovoltaic encapsulation light-converting carrier film 5 is encapsulated by the encapsulation film 2 and the glass 1. Among them, the battery cell 3 can be a Perc battery cell 3, an HJT battery cell 3, a TOPCon battery cell 3 or an IBC battery cell 3.
[0042] Furthermore, some embodiments of the present invention also provide an application of the above-mentioned light conversion bearing film for 0BB photovoltaic encapsulation in the preparation of a busbar-free solar cell module.
[0043] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0044] In the following examples and comparative examples, PE is LLDPE 7050 purchased from Sinopec; terpene resin is 803L terpene phenolic resin purchased from Guangzhou Linli New Materials Co., Ltd. Graft-modified resin is ESCOR5080 purchased from ExxonMobil; rare earth oxide is purchased from Shandong Desheng New Materials Co., Ltd., and rare earth organic complex is purchased from Xi'an Qiyue Biotechnology Co., Ltd.; EVA is Elvax EVA 3175 purchased from DuPont; POE is ENGAGE POE8407 purchased from Dow.
[0045] Example 1
[0046] The present embodiment provides a light-converting carrier film for 0BB packaging, which has an ultraviolet light absorption layer, an ultraviolet light conversion layer and an adhesive layer in sequence, and the thickness ratio of the ultraviolet light absorption layer, the ultraviolet light conversion layer and the adhesive layer is 1:1:2. The thickness of the light-converting carrier film for 0BB packaging is 100μm.
[0047] Among them, the ultraviolet light absorption layer includes 70 parts of base resin A, 30 parts of adhesive resin, 3 parts of mixing aids, and 0.2 parts of ultraviolet light absorber; the ultraviolet light conversion layer includes 80 parts of base resin B, 20 parts of adhesive resin, 3 parts of mixing aids, and 0.2 parts of ultraviolet light conversion agent; the bonding layer includes 70 parts of basic resin A, 30 parts of adhesive resin, 3 parts of mixing aids, and 0.2 parts of ultraviolet light absorber.
[0048] The base resin A and the basic resin B in the above raw materials are both 100 parts of polyethylene (PE), and the adhesive resin is a mixture of terpene resin and 1 part of grafted modified resin in a mass ratio of 1:1. The mixing auxiliary agent is a mixture of 1,1,3-tris(2-methyl-4-hydroxy-tert-butylphenyl)butane and triallyl isocyanurate (TAIC) in a mass ratio of 1:1.5. The ultraviolet light conversion agent is Eu 3+ Rare earth organic complexes and Eu 3+ The mixture is doped with rare earth oxides, the particle size of the ultraviolet light converter is less than 2 μm, and the ultraviolet light absorber is a mixture of 90 parts of nano-grade cerium oxide as a base material and 2-(2-hydroxy-5-methylphenyl)-benzotriazole as an auxiliary material in a mass ratio of 9:1.
[0049] The specific preparation process of the light-converting carrier film for 0BB encapsulation is as follows: each layer is mixed evenly according to the respective raw material ratios, and then put into the corresponding screws respectively. Among the raw materials corresponding to the ultraviolet light conversion layer, the ultraviolet light conversion agent is first coated with the matrix resin A to prepare a master batch, and then mixed evenly with other raw materials. The raw materials mixed evenly in each layer are extruded by multiple extruders respectively, and cast into a film in a multi-layer structure through a distributor. The screw temperature of the extruder corresponding to the ultraviolet light absorption layer is 180°C; the screw temperature of the extruder corresponding to the ultraviolet light conversion layer 200 is 200°C; the screw temperature of the extruder corresponding to the bonding layer 300 is 180°C; and the die head temperature is 200°C.
[0050] After cooling, the film is embossed, pre-crosslinked, and cut to obtain a three-layer light-converting carrier film, wherein the pre-crosslinking is performed by irradiating a short-wave ultraviolet lamp in the 250nm band with an irradiation energy of 2000mJ / cm 2 .
[0051] Example 2
[0052] The light-converting carrier film for 0BB packaging provided in this embodiment is different from that in Example 1 only in that the matrix resin A in the raw materials is ethylene-vinyl acetate copolymer (EVA), the matrix resin B is a mixture of polyethylene (PE) and ethylene-vinyl acetate copolymer (EVA) in a mass ratio of 7:3, and the remaining materials and methods are the same as in Example 1. After the respective resins and additives in each layer are mixed evenly, they are respectively put into the corresponding screws, and after co-extrusion casting, embossing, pre-crosslinking and slitting, a light-converting carrier film with a three-layer structure is prepared.
[0053] Example 3
[0054] The light-converting carrier film for 0BB packaging provided in this embodiment is different from that in Example 1 only in that the base resin A in the raw materials is a polyolefin elastomer (POE), the base resin B is a mixture of polyethylene (PE) and polyolefin elastomer (POE) in a mass ratio of 7:3, and the remaining materials and methods are the same as in Example 1. After the respective resins and additives in each layer are mixed evenly, they are respectively put into the corresponding screws, and after co-extrusion casting, embossing, pre-crosslinking and slitting, a light-converting carrier film with a three-layer structure is prepared.
[0055] Example 4
[0056] The light-converting carrier film for 0BB packaging provided in this embodiment is different from that in Example 1 only in that the matrix resin A and the matrix resin B in the raw materials are ethylene-vinyl acetate copolymer (EVA), and the remaining materials and methods are the same as in Example 1. After the resins and additives in each layer are mixed evenly, they are respectively put into the corresponding screws, and after co-extrusion casting, embossing, pre-crosslinking and slitting, a light-converting carrier film with a three-layer structure is prepared.
[0057] Example 5
[0058] The light-converting carrier film for 0BB packaging provided in this embodiment has the same materials and methods as Example 1, and the only difference is that after the resins and additives in each layer are evenly mixed, they are respectively put into the corresponding screws, and after co-extrusion casting, embossing and slitting, a light-converting carrier film with a three-layer structure is prepared.
[0059] Example 6
[0060] The light conversion carrier film for 0BB encapsulation provided in this embodiment is different from that in Embodiment 1 only in that the thickness of the ultraviolet light absorption layer, ultraviolet light conversion layer and adhesive layer are shown in Table 1, and the raw material ratio and preparation method are the same as those in Embodiment 1. The effects on the component efficiency and peeling force are also shown in Table 1.
[0061] Table 1
[0062] Serial number Total thickness / μm UV conversion layer / μm Adhesive layer / μm Component efficiency increase % Peel force N / cm 1 100 25 50 0.43 64 2 100 50 25 0.47 49 3 100 25 25 0.14 50 4 80 20 40 0.33 53 5 50 12.5 25 0.28 45
[0063] From the results in Table 1, it can be seen that when the thickness ratio of the ultraviolet light absorption layer, the ultraviolet light conversion layer and the adhesive layer is 1:1:2, the light conversion effect and the long-term durability effect are optimal during design.
[0064] Comparative Example 1
[0065] The raw material selection of the light-converting carrier film for 0BB packaging provided in this comparative example is the same as that of Example 1. The required materials in the corresponding proportions in the formula of Example 1 are all mixed together, stirred evenly, and then extruded by a single screw, and then cast, embossed, pre-crosslinked and cut to obtain a light-converting carrier film with a single-layer structure.
[0066] Comparative Example 2
[0067] The raw materials and preparation method of this comparative example are the same as those of Example 1. After the resins and additives in each layer are evenly mixed, they are respectively put into the corresponding screws, and after co-extrusion casting, embossing, pre-crosslinking and slitting, a light-converting bearing film with a three-layer structure is prepared, and the pre-crosslinked surface is the ultraviolet light absorbing layer.
[0068] The light-converting carrier films for 0BB encapsulation prepared in Examples 1 to 6 and Comparative Examples 1 to 2 were tested for haze, water vapor transmission rate, peeling force with the cell, light conversion efficiency after UV aging, transmittance, and module power. The following test methods were used for each performance test: peeling force: GB / T 2790-1995; transmittance: GB / T 2410-2008; water vapor transmission rate: GB / T21529-2008; module power: IEC61215; module power after DH1000h aging: IEC61215, where the module is a conventional double-glass PERC module. It should be noted that the test standard in Example 7 also refers to the above standard.
[0069] The test results are shown in Table 2.
[0070] Table 2
[0071]
[0072] It should be noted that the lamination appearance in the table is slight, very slight, and obvious. Figure 3 shown.
[0073] In summary, the above embodiments of the present invention use a base resin with a low water permeability value to improve the problem of poor long-term durability of the ultraviolet light converter under wet heat by multi-layer co-extrusion. By adjusting the formula of the light conversion carrier film and controlling the layer thickness ratio, its long-term durability, bonding strength, lamination appearance, and light transmittance meet the requirements of the photovoltaic industry. In addition, while meeting the performance requirements, the thickness of the light conversion carrier film can be as low as 20μm.
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A light-converting bearing film for 0BB photovoltaic encapsulation, characterized in that: It comprises a UV absorption layer, a UV conversion layer and a bonding layer formed by multi-layer co-extrusion in sequence; the thickness ratio of the UV absorption layer, the UV conversion layer and the bonding layer is 1:(1-2):(0.5-3); In parts by weight, the ultraviolet light absorbing layer comprises 60-90 parts of matrix resin A, 10-30 parts of adhesive resin, 1-5 parts of mixing aids and 0.01-2 parts of ultraviolet light absorber; the ultraviolet light conversion layer comprises 60-90 parts of matrix resin B, 10-40 parts of adhesive resin, 1-5 parts of mixing aids and 0.01-2 parts of ultraviolet light conversion agent; the adhesive layer comprises 50-90 parts of matrix resin A, 10-40 parts of adhesive resin, 1-5 parts of mixing aids and 0.01-2 parts of ultraviolet light absorber; The matrix resin A and the matrix resin B are independently selected from at least one of polyethylene, polyvinyl chloride, polystyrene, polypropylene, ethylene-vinyl acetate copolymer, ethylene-α-olefin copolymer, ethylene-methyl methacrylate copolymer or ethylene-methacrylic acid ionomer; The content of polyethylene in the matrix resin B is at least 70%.
2. The light-converting bearing film for 0BB photovoltaic encapsulation according to claim 1, characterized in that: The content of vinyl acetate in the ethylene-vinyl acetate copolymer is 10wt% to 33wt%; the olefin in the ethylene-α-olefin copolymer is selected from at least one of 1-pentene, 1-hexene, 4-methyl-1-hexene, 4-ethyl-1-hexene, 1-octene, 1-decene or 1-dodecene.
3. The light-converting bearing film for 0BB photovoltaic encapsulation according to claim 1, characterized in that: The matrix resin A and the matrix resin B are both polyethylene with a melt index of 1 to 6 g / 10 min at 190° C. / 2.16 kg.
4. The light-converting bearing film for 0BB photovoltaic encapsulation according to claim 3, characterized in that: The polyethylene is a linear low-density polyethylene, and the molecular weight of the polyethylene is 1000-4000.
5. The light-converting bearing film for 0BB photovoltaic encapsulation according to claim 1, characterized in that: The ultraviolet light conversion agent includes a light conversion agent of Eu 3+ Doped rare earth oxides, Pr 3+ Doped rare earth oxides, Nd 3+ Doped rare earth oxides, Sm 3+ Doped rare earth oxides, Gd 3+ Doped rare earth oxides, Tb 3+ Doped rare earth oxides, Dy 3+ Doped rare earth oxides, Ho 3+ Doped rare earth oxides, Er 3+ Doped rare earth oxides, Tm 3+ Doped with rare earth oxide or Yb 3+ doped with at least one of rare earth oxides; The adhesive resin includes at least one of a terpene resin or a grafted modified resin; the grafted modified resin is obtained by grafting and modifying a base resin and a grafted monomer through a melt reaction of free radical grafting, wherein the grafted monomer is selected from at least one of vinyl siloxane, an unsaturated monobasic acid, an unsaturated dibasic acid or an α, β unsaturated carbonyl compound, and the α, β unsaturated carbonyl compound is selected from at least one of maleic acid, fumaric acid, acrylic acid, methacrylic acid, α-methyl crotonic acid, cinnamic acid and anhydride, ester or salt derivatives of the above acids; The mixed auxiliary agent includes a first auxiliary agent and a second auxiliary agent; the first auxiliary agent includes at least one of phenols or amines, and the second auxiliary agent includes at least one of tripropylene trimer isocyanate, trimethylolpropane triacrylate, pentaerythritol tetraacrylate, trimethylolpropane trimethacrylate, triallyl cyanurate or di-trimethylolpropane tetraacrylate; The ultraviolet light absorber includes at least one of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, 2-(2-hydroxy-5-methylphenyl)-benzotriazole, a polymer of succinic acid and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol, or 1-(methyl)-8-(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate.
6. The light-converting bearing film for 0BB photovoltaic encapsulation according to claim 5, characterized in that: The particle size of the ultraviolet light conversion agent is less than or equal to 2 μm.
7. The light-converting bearing film for 0BB photovoltaic encapsulation according to claim 5, characterized in that: The adhesive resin has a melt index of greater than 15 g / 10 min at 190° C. / 2.16 kg.
8. The light-converting bearing film for 0BB photovoltaic encapsulation according to any one of claims 1 to 7, characterized in that: The thickness of the light-converting bearing film for 0BB photovoltaic encapsulation is 20 μm to 400 μm.
9. The light-converting bearing film for 0BB photovoltaic encapsulation according to claim 8, characterized in that: The thickness of the light-converting bearing film for 0BB photovoltaic encapsulation is 50 μm to 100 μm.
10. The light conversion bearing film for 0BB photovoltaic encapsulation according to any one of claims 1 to 7, characterized in that: The bonding layer is a pre-crosslinked surface.
11. A method for preparing a light-converting bearing film for 0BB photovoltaic encapsulation according to any one of claims 1 to 10, characterized in that: It includes: The formula materials of the corresponding layers are extruded by multiple extruders respectively, and cast into films in a multi-layer structure through a distributor.
12. The method for preparing the light-converting bearing film for 0BB photovoltaic encapsulation according to claim 11, characterized in that: The ultraviolet light conversion agent is coated with a layer of base resin to prepare a master batch, which is then mixed with other ingredients and extruded.
13. The method for preparing the light-converting bearing film for 0BB photovoltaic encapsulation according to claim 12, characterized in that: The screw temperature corresponding to the extrusion operation of the ultraviolet light absorbing layer is 90°C to 200°C; the screw temperature corresponding to the extrusion operation of the ultraviolet light conversion layer is 100°C to 220°C; the screw temperature corresponding to the extrusion operation of the bonding layer is 90°C to 200°C.
14. The method for preparing the light-converting bearing film for 0BB photovoltaic encapsulation according to claim 12, characterized in that: The screw temperature of the casting machine is 80°C to 250°C.
15. The method for preparing the light-converting bearing film for 0BB photovoltaic encapsulation according to claim 12, characterized in that: After the film is cast, it is embossed, pre-crosslinked and slit.
16. The method for preparing the light-converting bearing film for 0BB photovoltaic encapsulation according to claim 15, characterized in that: The pre-crosslinking is to irradiate the adhesive layer with a short-wave ultraviolet lamp in the wavelength range of 200nm to 280nm, and the irradiation energy is 500 to 5000mJ / cm 2 .
17. A busbar-free solar cell module, characterized in that: It includes the light-converting bearing film for 0BB photovoltaic encapsulation as described in any one of claims 1 to 10.
18. Use of the light-converting bearing film for 0BB photovoltaic encapsulation as claimed in any one of claims 1 to 10 in the preparation of a busbar-free solar cell module.
Citation Information
Patent Citations
Wavelength conversion layer on glass plate to enhance solar harvesting efficiency
CN104428907A
Wavelength conversion filter and method for manufacturing same, and solar cell module
CN107735700A